2022
DOI: 10.1111/jace.18298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ferroelectric polarization on piezo/photocatalysis in Ag nanoparticles loaded 0.5(Ba0.7Ca0.3)TiO3–0.5Ba(Zr0.1Ti0.9)O3 composites towards the degradation of organic pollutants

Abstract: A 0.5(Ba 0.7 Ca 0.3 )TiO 3 -0.5Ba(Zr 0.1 Ti 0.9 )O 3 (BCT-BZT) ceramic was studied for photocatalysis and piezocatalysis effects using dye degradation (methylene blue, rhodamine B, and methyl orange) and bacterial (Escherichia coli) disinfection from aqueous solution. To examine the effect of ferroelectric polarization, BCT-BZT powder was poled using the corona poling technique. Same time, BCT-BZT was converted into Ag/BCT-BZT composites as Ag induced surface plasmon resonance effect during photocatalysis. Pie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…29,30 Many metals such as Ag, Au, Pt, and Pd could be loaded on the piezocatalyst surface in order to develop the efficiencies of separation and migration of photo/piezoexcited charges. 13,23,29,31 In the literature, various different semiconductors such as perovskites, metal nitrides, metal suldes etc. can show piezoelectric properties depending on their crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Many metals such as Ag, Au, Pt, and Pd could be loaded on the piezocatalyst surface in order to develop the efficiencies of separation and migration of photo/piezoexcited charges. 13,23,29,31 In the literature, various different semiconductors such as perovskites, metal nitrides, metal suldes etc. can show piezoelectric properties depending on their crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…[33] Studies have shown that ferroelectric materials with narrow bandgaps and high absorption coefficients have great application potential in the photovoltaic industry, and can be designed into multifunctional photovoltaic devices such as solar cells, [1,9,34] photodetector, [22,[35][36] and photocatalysis. [37][38][39] In photovoltaic material applications, the performance stability of inorganic materials is better than organic materials. [40][41][42] Moreover, in organic photovoltaic materials, the separation of electron-hole pairs is not taken place directly with the absorption of light which needs to be separated with the help of an external field.…”
Section: Introductionmentioning
confidence: 99%
“…[ 33 ] Studies have shown that ferroelectric materials with narrow bandgaps and high absorption coefficients have great application potential in the photovoltaic industry, and can be designed into multifunctional photovoltaic devices such as solar cells, [ 1,9,34 ] photodetector, [ 22,35–36 ] and photocatalysis. [ 37–39 ]…”
Section: Introductionmentioning
confidence: 99%
“…Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O 3 (BCT-BZT) is one of the potential materials for various emerging energy harvesting and catalysis fields. [19][20][21][22][23][24] It has Curie temperature of around 85 C and has interesting electrical properties. A large number of literature is evidence of its excellent properties.…”
mentioning
confidence: 99%